Pengaruh Work Life Balance, Stres Kerja dan Kompensasi terhadap Kepuasan Kerja (Studi pada Warung Parikaton) - sa’diyah, Chalimatus; Salim, Muhammad Agus; Millaningtyas, Restu (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The objective of this study is to determine the influence of work-life balance, work stress, and remuneration on the job satisfaction of Warung Parikaton employees both partially and simultaneously. The study uses a quantitative approach, and the population used was Warung Parikaton employees. The sample used was a saturated sample, meaning all of the employees in the restaurant were used as a sample. The results of this study show that work-life balance, work stress, and job satisfaction are simultaneously affected by coefficient of determination, coefficient of determination, instrument testing (validity and reliability test), normality test, classical assumption test (mucticolinierity and heteroscedasticity test), multiple linear regression analysis, hypothesis test (t test and F test), and coefficient of determination test. Keywords: Work-life balance, work stress, compensation and job satisfaction